Application of ISAK 35 to the Presentation of Financial Reports of the Manado Diocese of the Catholic Church - Lomboan, Meiva Fransiska; Saerang, David Paul Elia; Budiarso, Novi Swandari (Yayasan Widyantara Nawasena Raharja, 2024)
This study aims to determine the existing forms of financial reporting and to find out stages, impacts and driving factors of the process of implementing ISAK 35 on the presentation of financial reports of the Manado Diocese of the Catholic Church based on the institutional theory of the form of coercive isomorphism and the Edward III model theory, namely communication, resources, disposition, bureaucratic structure. This study uses the method descriptive qualitative where data collection was carried out by means of interviews and documentation studies. The results show that the policy for implementing financial accounting information systems is not yet fully in accordance with applicable accounting standards. The organization has not fully adhered to the standard of ISAK 35. Financial records are processed using existing financial applications. By the aspect of resources, the attitude of the implementers still shows that the implementers still have minimal/not yet adequate knowledge about the accounting system created and communication between implementing agents is not yet optimal. The indicators in the bureaucratic structure variable in the form of SOPs have been achieved well because in 2019 the Manado Diocese has created a Financial Guideline that must be implemented by every parish, although in practice it is not yet perfect. In its implementation, there are still obstacles from a practical perspective, such as human error, hardware weaknesses, software weaknesses and system weaknesses. Efforts to overcome obstacles include continuing to update applications that have been created based on the latest standards and providing regular training materials that are packaged easily so that the attitude of the application implementing agents themselves can accept the new policy and those responsible for parish finances must be wiser and adhere to diocesan policies to produce financial reports that are transparent, accountable, and trustworthy.